Global longitudinal strain is a better metric than left ventricular ejection fraction: lessons learned from cancer therapeutic-related cardiac dysfunction. (March 2020) - Patel, Jay; Rikhi, Rishi; Hussain, Muzna; Ayoub, Chadi; Klein, Alan; Collier, Patrick; Moudgil, Rohit
Abstract : Purpose of the review: This review aims to highlight the utility of global longitudinal strain (GLS) in cancer therapeutic-related cardiac dysfunction (CTRCD), with an attempt to stipulate that GLS might be a better measure than left ventricular ejection fraction (LVEF). Recent findings: Increasingly, GLS quantification has been employed in various cardiovascular diseases especially with its ability to detect left ventricular dysfunction subclinically, even before a change in LVEF is visualized. In fact, several studies reveal that GLS may be a superior predictor of mortality and morbidity than LVEF in this context. A recent metaanalysis supported the prognosticating value of GLS in CTRCD, however, endorsed the need for larger multicenter studies to establish the value of this metric. Studies in other cardiovascular disease processes showed GLS as a better metric than LVEF. Summary: GLS has been heralded as a new echocardiographic measure that can detect subclinical cardiac disease. At a minimum, GLS can provide incremental value in prognosticating, diagnosing, and predicting LVEF recovery and at best, a better measure of left ventricular dysfunction.